Penthrox alone versus Penthrox plus periprostatic infiltration of local analgesia for analgesia in transrectal ultrasound‐guided prostate biopsy. Issue 3 (5th February 2015) - Huang, Sean; Pepdjonovic, Lana; Konstantatos, Alex; Frydenberg, Mark; Grummet, Jeremy
Abstract: Background: The objective of this study was to compare pain intensity in patients undergoing transrectal ultrasound (TRUS)‐guided biopsy of the prostate with Penthrox alone compared with Penthrox plus periprostatic infiltration of local analgesia (PILA). Method: Seventy‐two subjects participated in this study after receiving appropriate education. Forty‐two patients self‐administered inhaled Penthrox (3 mL methoxyflurane) alone for analgesia (Group A), followed by 30 patients who self‐administered Penthrox and received PILA with 5 mL of 2% lignocaine. All subjects had TRUS biopsy performed. Immediately after the procedure, patients were asked to rate their pain intensity using a numerical verbal rating scale from 0 to 10. Results: Baseline characteristics of the two groups were similar. Patients in Group B reported significantly lower post TRUS biopsy median pain intensity of 2 (1–3) compared with Group A subjects who reported a median post TRUS biopsy pain intensity of 3 (2–5) ( P = 0.014). A total of 72 men underwent TRUS‐guided biopsy. All patients indicated they would be happy to have another TRUS‐guided prostate biopsy in the future. Conclusion: Our study shows that Penthrox plus PILA shows promise as an efficacious and easily tolerated analgesic technique for outpatient TRUS biopsy, keeping resource use to a minimum. Planning for a multi‐centre, double‐blind randomized control trial comparing Penthrox plus PILA with PILA alone is presently underway.